Evaluation of World Bank Programs in Afghanistan 2002-11. (Independent evaluation studies., 2013)
This report evaluates the outcomes of World Bank Group support to Afghanistan from 2002-11. Despite extremely difficult security conditions, which deteriorated markedly after 2006, the World Bank Group has commendably established and sustained a large program of support to the country. The key messages of the evaluation are: While World Bank Group strategy has been highly relevant to Afghanistans situation, beginning in 2006 the strategies could have gone further in adapting ongoingprograms to evolving opportunities and needs, and in programming activities sufficientto achieve the objectives of the pillars in those strategies. Overall, Bank Group assistance has achieved substantial progress toward most ofits major objectives, although risks to development outcomes remain high. Impressive results have been achieved in public financial management, public health, telecommunications, and community development; substantial outputs have alsobeen achieved in primary education, rural roads, irrigation, and microfinanceallstarted during the initial phase. Bank assistance has been critical in developingthe mining sector as a potential engine of growth. However, progress has beenlimited in civil service reform, agriculture, urban development, and private sectordevelopment. The Bank Groups direct financial assistance has been augmented effectively byanalytic and advisory activities and donor coordination through the AfghanistanReconstruction Trust Fund. Knowledge services have been an important part ofBank Group support and have demonstrated the value of strategic analytical work, even in areas where the Bank Group may opt out of direct project financing. With the expected reduction of the international presence in 2014, sustainabilityof development gains remains a major risk because of capacity constraints andinadequate human resources planning on the civilian side. To enhance program effectiveness, the evaluation recommends that the Bank Group help the government develop a comprehensive, long-term human resources strategy for the civilian sectors; focus on strategic analytical work in sectors that are high priorities for the government; assist in the development of local government institutions and, in the interim, support the development of a viable system for servicedelivery at subnational levels; assist in transforming the National Solidarity Program into a more sustainable financial and institutional model to consolidate its gains; help strengthen the regulatory environment for private sector investment; and scale up IFC and MIGA support to the private sector. Chapter AbstractsChapter 1This chapter examines the country context, including continuing conflict and insecurity, poverty, and the role of development partners and non-state actors (civil society and humanitarian organizations) in Afghanistan. It examines coming transitions in security arrangements, including political and economic transitions. It outlines the evaluation methods used, as well as limitations. Chapter 2This chapter deals with the World Bank Group strategy and program, the Bank Groups operational program, portfolio performance, analytic and advisory activities review, the Afghanistan Reconstruction Fund, and the new Interim Strategy Note, as well as previous Transitional Support Strategies and ISNs. Chapter 3This chapter examines the building of state capacity and state accountability to its citizens, specifically issues such as results and shortcomings in public financial management, public sector governance, and health and education. The World Bank Group contribution is highlighted. Risks to development outcomes are discussed. Chapter 4This chapter examines the issue of promoting growth in the rural economy and improving rural livelihoods, including sectors such as rural roads, agriculture and water. The National Solidarity Program and the Bank Groups contribution to it are discussed. Risks to development o.